Analysis of the porcine APOA2 gene expression in liver, polymorphism identification and association with fatty acid composition traits. (14th June 2016) - Ballester, M.; Revilla, M.; Puig‐Oliveras, A.; Marchesi, J. A. P.; Castelló, A.; Corominas, J.; Fernández, A. I.; Folch, J. M.
Summary: APOA2 is a protein implicated in triglyceride, fatty acid and glucose metabolism. In pigs, the APOA2 gene is located on pig chromosome 4 (SSC4) in a QTL region affecting fatty acid composition, fatness and growth traits. In this study, we evaluated APOA2 as a candidate gene for meat quality traits in an Iberian × Landrace backcross population. The APOA2 :c.131T>A polymorphism, located in exon 3 of APOA2 and determining a missense mutation, was associated with the percentage of hexadecenoic acid [C16:1(n–9)], linoleic acid [C18:2(n–6)], α ‐linolenic acid [C18:3(n–3)], dihomo‐gamma‐linolenic acid [C20:3(n–6)] and polyunsaturated fatty acids (PUFAs) in backfat. Furthermore, this SNP was associated with the global mRNA expression levels of APOA2 in liver and was used as a marker to determine allelic expression imbalance by pyrosequencing. We determined an overexpression of the T allele in heterozygous samples with a mean ratio of 2.8 ( T/A ), observing a high variability in the allelic expression among individuals. This result suggests that complex regulatory mechanisms, beyond a single polymorphism ( e.g . epigenetic effects or multiple cis‐acting polymorphisms), may be regulating APOA2 gene expression.